The role of poroelasticity on the biomechanics of the intervertebral disc : a finite element study - Castro, André (2013)
The major goal for the present work is to evaluate a biomimetic Finite Element (FE) model of the Intervertebral Disc (IVD). Recent studies have emphasized the importance of an accurate biomechanical modeling of the IVD, which is a highly complex biphasic medium. A novel biphasic poroelastic model was implemented and coupled with Wilson’s model (2005) for biphasic osmotic swelling behavior. Numerical tests were devoted to the analysis of the time- dependent behavior of the IVD. The results show good agreement with literature experimental data (Heuer et al., 2007 or O’Connell et al., 2011) and also with other numerical studies (Galbusera et al., 2011). In brief, this in-development IVD FE model aims to be a valuable tool to study the biomechanics of the IVD and its pathways for degeneration.